The construction of emotional competency test kits for preschoolers - Meria Susanti; Maria Goretti Adiyanti (Institut Agama Islam Negeri Langsa, 2022)
Emotional competence is one of the essential abilities to be possessed by children. Children with good emotional competence will be able to understand their emotions toward themselves or others well. This competence will help children adjust to and interact well in their social environment. This study aims to develop an emotional competency test kit for preschoolers. The items on this test kit are based on the theory of emotional competence presented by Denham. This test kit consists of eight-story scenarios that trigger the appearance of emotions in the child. The validity test on this test tool used expert judgment on 17 people consisting of early childhood care and education practitioners, child psychologists, parents, and Master of Professional Psychology students in Education, with the results of the analysis using Aiken’s V. Aiken’s V analysis results, obtained a validity coefficient of 0.71-0.95. Meanwhile, the results of the analysis of the test kit trial of 96 subjects obtained a reliability coefficient of emotional competency test kits of 0.801. This study showed that this test kit has good validity and reliability and can be used to measure emotional competence in preschoolers.